Separately excited DC motor control method using MATLAB software (Simulink) and interface with graphical user (GUI) / Hasbibullah Omar - Omar, Hasbibullah (2010)
This project is to investigate the characteristic of DC motor speed by using MATLAB Software. The speed of the DC motor can be controlled using Armature Voltage Control (Va), Field Resistance Control (Rf) and Armature Resistance Control (Ra). The Separately Excited DC motor will be simulated by using MATLAB Simulink. The three control methods as stated above will be used in order to investigate the motor speed characteristic. In addition, the MATLAB Graphical User Interface (GUI) was also used in this project to display the output from the simulation.